THU0586 Agreement of Patient and Physician Global Assessment of Disease Activity in Adult Onset Still's Disease. (15th July 2016) - Kalyoncu, U.; Kasifoglu, T.; Kisacik, B.; Oksuz, M.F.; Omma, A.; Bes, C.; Cinar, M.; Pamuk, O.N.; Kucuksahin, O.; Akar, S.; Aksu, K.; Yildiz, F.; et al.
Abstract : Background: There is not valid outcome measures for assessment Adult onset Still's disease (AOSD) activity. The patients or physicians global view is relevant way to assess this kind of complex diseases. However, it is well known that there is discordance between patient and physician perspective for disease activity in different inflammatory diseases. Objectives: Objective of this study was to evaluate agreement of patient and physician perspective in AOSD patients. Methods: We conducted a cross-sectional, multicenter study for assessment of disease activity in AOSD patients. All AOSD patients were fulfilled Yamaguchi criteria. For every center, at least 20% of AOSD patients had to be an active state according to physician assessment. Age, sex, disease duration, current disease symptoms was recorded. Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), leucocyte, and ferritin level also recorded. Visual analog scale (VAS) (0–10 cm) used for physician and patient global assessment of disease activity. Disease activity status were also assessed by likert scale (as remission, low, moderate, severe, and more severe disease activity) for both patients and physician perspective. Patient global assessment VAS and physician global assessment were correlated by correlation coefficient (r). Agreement of disease activity level for patient and physician perspective were calculated with kappa. Kappa >0.6 was accepted as significant. Results: One hundred thirty (83, 63.4% female) AOSD patients were enrolled. Mean age was 38 (14) years old and median disease duration was 3 years (0–29). Currently AOSD symptoms followed; fever 34 (26.2%), rash 28 (21.5%), arthritis 31 (23.8%), arthralgia 60 (46.2%), sore throat 28 (21.5), myalgia 42 (32.3), lympadenopathy 12 (9.2%), splenomegaly 17 (13.1%), hepatomegaly 7 (5.4%), pleuritic 3 (2.3%), hemophagocytic syndrome 2 (1.5%). ESR 47.7%, CRP 43.8%, ferritin 27.0%, and leucocyte 43.1% were higher than upper limit. Mean patient global assessment VAS was 3.53 (3.25), and mean physician global assessment VAS was 2.71 (2.95). Correlation coefficient (r) of patient and physican global VAS was 0.89. There was excellent agreement according to severe/more severe disease activity at patient and physician level (kappa 0.88 (CI 95% 0.79–0.98). There was also good to excellent agreement according to low disease activity/remission at patient and physician level (kappa 0.74 (CI 95% 0.62–0.86). Conclusions: Although, features of AOSD seems more complex with constitutional symptoms, joint or reticuloendothelial system involvement, patients and physicians assess level of disease activity similarly. We thought, this results will be helpful for procedure of new composite index in AOSD. Disclosure of Interest: None declared